Has Financial Policy Intervention Benefited Local Society Affected by Natural Disaster?: Questioning the Utilitarian Approach - Ketut Sukawati Lanang Putra Perbawa (Udayana Journal of Law and Culture, 2019)
Mount Agung eruptions have an impact on economic losses, especially the banking sector in Bali. Entrepreneurs and bank debtors, especially in Karangasem Regency and its surroundings, ask for relief from the implementation of the provisions of their credit agreements in terms of time, interest and also obligations performance. It is a legal research that focuses on analyzing the utilitarian approach used by the Indonesian Financial Services Authority (Otoritas Jasa Keuangan/OJK) in the form of Banking-relaxation policy in supporting the local society who affected by natural disaster. It has been concluded that local society who affected by the eruption of Mount Agung in Karangasem Regency Bali may use ‘force majeure’ to suspend their obligation performance in any economic matters, including loan banking. In addressing this issue, OJK plays a role by issuing financial policy for the 3 years period that is expected to give a margin of appreciation for local society to re-arrange their economic situation after the disaster. Such policy, seems has not properly been implemented by all banks in related area. Therefore, a utilitarian approach that inspired the OJK financial relaxation policy should be improved by taking into consideration the concerns on cultural-economic issues, the real declining and uncertain situation of the local economy, and the fragile tourism industry in Karangasem regency.